2020
DOI: 10.1108/qram-05-2019-0062
|View full text |Cite
|
Sign up to set email alerts
|

Controlling outsourced management accounting to build legitimacy

Abstract: Purpose This paper aims to explore controls within an inter-organisational relationship involving outsourced management accounting services from the contractor’s perspective. Design/methodology/approach Qualitative data from within the relationship are analysed in a legitimacy-theory framework, illustrating how controls within the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…1. Introduction Interorganizational control (Lepistö et al, 2020;Dekker et al, 2018) and planned organizational changes (Lukka and Partanen, 2014;Chenhall and Euske, 2007;Huy, 2001a) as purposeful actions that involve an alteration of multiple organizational elements (Agndal and Nilsson, 2019;Huy, 2001a), have interested researchers for a long time. This study combines these two research areas by focusing on the time and temporal management of a financial accounting outsourcing (FAO) transition.…”
Section: Financial Accounting Outsourcing Transitionmentioning
confidence: 99%
See 2 more Smart Citations
“…1. Introduction Interorganizational control (Lepistö et al, 2020;Dekker et al, 2018) and planned organizational changes (Lukka and Partanen, 2014;Chenhall and Euske, 2007;Huy, 2001a) as purposeful actions that involve an alteration of multiple organizational elements (Agndal and Nilsson, 2019;Huy, 2001a), have interested researchers for a long time. This study combines these two research areas by focusing on the time and temporal management of a financial accounting outsourcing (FAO) transition.…”
Section: Financial Accounting Outsourcing Transitionmentioning
confidence: 99%
“…The FAO literature has focused on staff attrition in offshoring (Nicholson and Aman, 2012), contract monitoring of the FAO relationship (Anguelov, 2016), accounting outsourcing turnback (Maelah et al, 2010), legitimacy building through outsourced management accounting (Lepistö et al, 2020) and the development of FAO through shared service centers (Hyvönen et al, 2012). To understand the FAO transition process, scholars have built models and identified stages (Nicholson et al, 2006).…”
Section: Management Interventions In Relation To the Financial Accoun...mentioning
confidence: 99%
See 1 more Smart Citation
“…Smith et al, 2005), and models both the costs and the benefits of the decisions through transaction costs determined by the asset specificity, environmental and behavioral uncertainty, as well as the frequency of transactions (Widener and Selto, 1999). While TCE-literature has acknowledged that cooperation with a service provider enables development of the relationship and more transactions to be outsourced (Speklé, 2001), and recent research has shown how the service provider may contribute the development of the relationship by its legitimating efforts (Lepistö et al, 2020), earlier research has provided limited understanding of the influence of outsourcing accounting functions on firm performance. RBV is premised on strategic resources being heterogeneously distributed across firms (Barney, 1991).…”
Section: Outsourcing In Accounting Researchmentioning
confidence: 99%
“…To minimize risk, creditors support the prudent presentation of financial statements. Therefore, the level of conflict of interest can affect the implementation of the principle of prudence contained in the presentation of financial statements (Lepistö et al, 2020;S. N. Sari & Agustina, 2021).…”
Section: Conflict Of Interestmentioning
confidence: 99%